Voltage Stability Improvement of Balanced Radial Distribution Networks - Pratik, Kumar (My University, 2016)
An approach for the optimal placement of DG and Capacitor of proper size in Radial distribution networks (RDNs) is presented. At the beginning of the Electrical Power system, the active and reactive power losses had been a greater challenge. Compensating the power of the system has become the prime area to improve the system stability. The Distributed Generator and Capacitor allocation problem involves determining the optimal placements and also the selection of the perfect size of the DG and capacitor. Load flow is performed at first to compute the actual losses of the system and voltages at different nodes without compensation called base case. In the proposed technique, the LSF (Loss sensitivity factor) is used to determine the optimal location of DG& capacitor. The optimal sizes of the DG and Capacitor have been determined by analytical approach. To justify the objective of the method after installing the DG and Capacitor, the load flow is performed again at the identified nodes. The proposed scheme is tested on standard 33node and 69 node RDNs.
Master of Engineering- Power Systems
Keywords: Radial distribution system; Voltage stability index; Loss sensitivity factor